Giant hibernoma of the thoracic pleura and chest wall - Jaroszewski, Dawn E (Baishideng Publishing Group Co., Limited, 2013)
Hibernoma is a rare tumor containing prominent brown adipocytes that resemble normal brown fat. Brown fat (versus white fat) is predominantly found in hibernating mammals and infants. Brown fat adipocytes contain a higher number of small lipid droplets and a much denser concentration of mitochondria. The tumor can occur in a variety of locations however the extremities, followed by the head and neck, have been the most common sights. All variants of hibernoma described have followed a benign course with the majority presenting as a small, lobulated, nontender lesions. We present a case of a giant hibernoma arising from the pleura which invaded the intra and extra-thoracic chest.